Development of downstream processes for pigment valorization: a step towards blue biorefinery - Vaz, Bárbara Maria Correia (2021)
The guidelines of The 2030 Agenda for Sustainable Development were very clear. New strategies need to be found to ensure a sustainable future. In this way, marine resources emerge as natural and renewable feedstocks to integrate a blue biorefinery framework and a circular economy approach. Through biomass conversion an integrated production of biofuels and value-added compounds can be designed, allowing the recovery of multiple compounds with lower environmental impacts and a sustainable economic growth. Pigments are natural compounds used in high-end applications due to their colour and high biological interest that can be found in several marine resources. However, the conventional techniques to recover them require the use of complex and time-consuming methodologies that may lead to the degradation and/or loss of stability of the compounds, high energy consumption, and low yields of extraction. Alternative solvents such as aqueous solutions of surfactants and ionic liquids (ILs) appear as more sustainable options that can improve thermal and chemical stability of pigments, obtain higher extraction yields, while minimizing the environmental impacts of the process. In this work, two procedures were developed to recover different pigments using alternative solvents, to overcome the bottlenecks found in the conventional methodologies. In the first work, a solid-phase extraction technique was used to fragmentate chlorophylls from xanthophyll. Then, to elute chlorophylls from AmberLite™ HPR900 OH resin, aqueous solutions of ILs revealed to be efficient solvents to valorize simultaneously xanthophyll and chlorophylls while reusing the resin in several new cycles of purification. The second work focused on the extraction of bacterioruberin pigment from Haloferax mediterranei with aqueous solutions of surfactants, being the non-ionic class the one that showed higher extraction yields. Moreover, the purification of bacterioruberin was also addressed by inducing a simple precipitation with ethanol as anti-solvent to recover proteins as a second added-value compound. In both works easy to implement and environmentally friendly procedures using water-based solvents were successfully proposed, being the operational conditions optimized to reduce both economic and environmental impacts, and to reach higher yields.